2002
DOI: 10.1073/pnas.222313099
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of fungus-growing termites and their mutualistic fungal symbionts

Abstract: We have estimated phylogenies of fungus-growing termites and their associated mutualistic fungi of the genus Termitomyces using Bayesian analyses of DNA sequences. Our study shows that the symbiosis has a single African origin and that secondary domestication of other fungi or reversal of mutualistic fungi to a freeliving state has not occurred. Host switching has been frequent, especially at the lower taxonomic levels, and nests of single termite , is derived with two independent origins. Despite repeated ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
510
1
6

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 382 publications
(534 citation statements)
references
References 31 publications
17
510
1
6
Order By: Relevance
“…This would imply that the fungal symbionts have not been selected to invest in antagonistic traits, but this prediction remains to be tested. The few studies that have addressed within-nest variation of fungal symbionts, have found single cultures within single nests (Aanen et al 2002;Katoh et al 2002), consistent with the hypothesis that recurrent bottlenecking within nests reduces fungal within-nest variation. However, more research is needed to confirm this hypothesis, especially for species with multiple separate fungus combs per nest.…”
Section: Discussionmentioning
confidence: 60%
“…This would imply that the fungal symbionts have not been selected to invest in antagonistic traits, but this prediction remains to be tested. The few studies that have addressed within-nest variation of fungal symbionts, have found single cultures within single nests (Aanen et al 2002;Katoh et al 2002), consistent with the hypothesis that recurrent bottlenecking within nests reduces fungal within-nest variation. However, more research is needed to confirm this hypothesis, especially for species with multiple separate fungus combs per nest.…”
Section: Discussionmentioning
confidence: 60%
“…They developed a sophisticated mutualistic symbiosis with a kind of fungi ( Termitomyces spp., Basidiomycotina), which they cultivate on combs constructed from faecal material within their nests (Johnson et al 1981; Wood and Thomas 1989). This symbiosis firstly occurred with no reversions to free-living states (Aanen et al 2002) at least 31 million years ago (Nobre et al 2011) and is obligate for both partners: the termites provide a constant, highly regulated growth environment for their fungal symbionts, while the fungi provide food for the termites. Fungi are cultivated on combs constructed from faecal material within termites’ nests (Wood and Thomas 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Through horizontal transmission, a given fungal species can establish symbiotic relationship with several termite species within a genus (Aanen et al 2002). Evidence for the dominant role of horizontal transmission of Termitomyces genotypes has been found in sequence analyses of Termitomyces .…”
Section: Macrofungi In Mutualistic Relationships With Animalsmentioning
confidence: 99%
“…Furthermore, by analyzing the relationships between several termite species from Asia and their associated Termitomyces fungi, Taprab et al (2002) discovered that the symbiotic fungal species and their distribution paralleled those of the termites. Similarly, Aanen et al (2002) investigated 32 termite species in 9 genera from Asia and Africa and their associated Termitomyces fungi. The results showed that the symbiosis has a single African origin, with no evidence for secondary domestication of other fungi or the reversal of mutualistic fungi to a free-living state.…”
Section: Macrofungi In Mutualistic Relationships With Animalsmentioning
confidence: 99%
See 1 more Smart Citation